Staphylococcus aureus activates NRLP3-dependent IL-1β secretion from human conjunctival goblet cells using α toxin and toll-like receptors 2 and 1 - Li, Dayu; Hodges, Robin; AukrustNaqvi, Maria; Bair, Jeffrey; Bispo, Paulo J. M.; Gilmore, Michael S.; Gregory-Ksander, Meredith; Dartt, Darlene A. (Frontiers in Cellular and Infection Microbiology, 2023)
We used cultured human conjunctival goblet cells to determine (i) whether the toxigenic S. aureus- induced activation of the epithelial goblet cells requires two signals to activate the NLRP3 inflammasome, (ii) if one signal is mediated by TLR1, TLR2, or TLR6, and (iii) if the S. aureus toxin α toxin is another signal for the activation of the inflammasome and secretion of mature IL-1β. Cultured cells were incubated with siRNA to knock down the different TLRs. After stimulation with toxigenic S. aureus RN6390, pro-IL-1β synthesis, caspase-1 activity, and mature IL-1β secretion were measured. In a separate set of experiments, the cells were incubated with toxigenic S. aureus RN6390 or mutant S. aureus ALC837 that does not express α toxin with or without exogenous α toxin. A gentamicin protection assay was used to determine if intracellular bacteria were active. We conclude that α toxin from toxigenic S. aureus triggers two separate mechanisms required for the activation of the NLRP3 inflammasome and secretion of mature IL-1β. In the first mechanism, α toxin secreted from internalized S. aureus produces a pore, allowing the internalized bacteria and associated pathogen-associated molecular patterns to interact with intracellular TLR2 and, to a lesser extent, TLR1. In the second mechanism, α toxin forms a pore in the plasma membrane, leading to an efflux of cytosolic K+ and influx of Ca2+. We conclude that α toxin by these two different mechanisms triggers the synthesis of pro-IL-1β and NLRP3 components, activation of capase-1, and secretion of mature IL-1β to defend against bacterial infection.